Association between colchicine resistance and vitamin D in familial Mediterranean fever. (9th August 2015) - Ozer, Ismail; Mete, Turkan; Turkeli Sezer, Ozlem; Kolbasi Ozgen, Guyem; Kucuk, Gultekin Ozan; Kaya, Coskun; Kilic Kan, Elif; Duman, Gulhan; Ozturk Kurt, Hacer Pinar
Abstract: Although colchicines are the only effective treatment of familial Mediterranean fever (FMF), resistance to colchicines (CR) which is observed in up to 30% of the patients is still a problem. Clinically, resistance to colchicine is defined as three or more attacks within the last 6 months period while using ≥2 mg/day colchicine. Previous studies have shown decreased vitamin D levels in FMF patients compared with healthy controls. The aim of this study is to evaluate whether vitamin D levels differ between CR and non-CR FMF patients. This study included 64 FMF patients who were being followed in Nephrology Clinic of Samsun Research and Education Hospital for at least 1 year. FMF was diagnosed according to the criteria defined by Livneh et al. Serum 25-hydroxy vitamin D (25-OHD) concentration (ng/mL) was detected in all FMF patients who were not in an acute attack period. From 64 patients 29 were accepted as CR. Mean 25-OHD level was 9.39 ± 1.00 ng/mL in CR patients and 18.48 ± 1.09 ng/mL in colchicine responsive patients ( p < 0.001). Plasma vitamin D levels were significantly lower in colchicine resistant patients. Vitamin D deficiency may be a factor in etiopathogenesis of CR. Studies in larger patient samples that particularly evaluate the response to vitamin D replacement in CR FMF patients are needed.